Joint kinetics in rearfoot versus forefoot running: Implications of switching technique - Stearne, S. M.; Alderson, J. A.; Green, B. A.; Donnelly, C. J.; Rubenson, J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: To better understand the mechanical factors differentiating forefoot and rearfoot strike (RFS) running, as well as the mechanical consequences of switching techniques, we assessed lower limb joint kinetics in habitual and imposed techniques in both groups.